Patterns of R&D and Growth Performance: Can a Technological Follower Be Converted Into an Economic Leader? - Argentino Pessoa; Mario Silva (European Regional Science Association (ERSA), 2006)
It is well known that researchers in several traditions have argued that innovation is essential to ensure countries' economic growth (Schumpeter, 1912; Freeman, 1987; Pavitt, 1982; Romer, 1990; Jones, 1995). At the same time, others researchers have stressed the role of imitative capacity in economic catching-up (Rosenberg, 1963; Abramovitz, 1986; Fagerberg, 1987). Simultaneously, for a great lot of countries economic growth has become one of the most significant policy commitments. Accordingly, although with very different results, several countries have vastly increased their economic and policy commitments to innovation and have made investments in their innovative capacity, and in their levels of R&D expenditures. Furthermore, R&D intensity, the structure of R&D expenditures and the productivity of R&D outlays show a remarkable diversity across countries. Our paper uses this diversity and the lessons of the past three decades to shed some light on the relationship between productivity and technological change and aims to answer the following questions: How was the productivity in economic miracles propelled by a technological change? What are the reasons why it seems so easy for some few countries — and so difficult for a lot of others — to catch-up with the levels of productivity of the world technological frontier? So, in this paper we investigate the patterns of development in national innovative capacity, focusing on the country level investments in R&D, and in the examination of the patent counts, in a broad sample of countries that include the leaders and the followers in catching up to the world's leading countries. The institutional configurations, and national policy decisions that shape the different behaviour of some follower nations in terms of productivity and innovative output, are also studied.
Keywords: 330